DEVELOPMENT OF ACHIEVEMENT MOTIVATION TRAINING MODULE TO IMPROVE STUDENT ACADEMIC RESILIENCE IN DISASTER AREAS - Suud, Fitriah M.; Uyun, Muhamad; Na'imah, Tri (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Students living in disaster-prone areas often experience obstacles to increasing enthusiasm for learning and a lack of resilience, especially academic resilience. This research aims to develop an Achievement Motivation training module to improve Student Academic Resilience. This research was conducted with a 4D model research and development model consisting of 4 stages, namely define, design, develop, and disseminate. The respondents were disaster-prone students in Central Sulawesi. The data analysis technique used is the first quantitative descriptive of the problem profile of students' academic resilience. Second, qualitative descriptive data analysis was used for FGD result analysis to design achievement motivation training models. The results of the define stage research found student problems related to academic resilience. Descriptive analysis finds aspects of academic resilience, namely problem-facing ability, self-adjustment, resilience, and problem-solving ability. The results of the research design stage have formulated an Achievement motivation Training module for disaster-prone students. The study recommends the primary role of teachers in helping students achieve higher levels of academic resilience. One of the recommended programs is achievement motivation training, which can be adopted by teachers through classical and group approaches.